Application of next-generation sequencing in thalassemia screening: A systematic review and meta-analysis - Xingyi Fang; Yi Gong; Yanlin Ma; Yuanhua Huang (Asian Pacific Journal of Tropical Medicine, 2023)
Objective: To evaluate the value of next-generation sequencing (NGS) in the prevention and management of thalassemia. Methods: A systematic search was performed in eight databases including China Biomedical Literature Database, Chinese National Knowledge Infrastructure, Chinese Scientific Journals Database, Wanfang database, PubMed, EMBASE, Web of Science, and Cochrane Library from the inception to 1 June 2022. Stata 17.0 and Review Manager 5.4 were used for the meta-analysis. Results: Nine studies containing 14794 participants were included in the meta-analysis. Compared with the routine genetic testing (including Gap-PCR and reverse dot blot), NGS had higher detection rates in screening thalassemia (RR 1.22, 95% CI 1.13-1.31, P<0.01), particularly for the α-thalassaemia mutation carriers (RR 1.24, 95% CI 1.07-1.44, P<0.01). However, no significant difference was found in the screening of β-thalassemia (RR 1.10, 95% CI 0.99-1.23, P>0.05). Conclusions: Compared with routine genetic testing, NGS had a higher detection rate in general, particularly in the detection of α-thalassemia.